PERAN FUNGI MIKORIZA ARBUSKULAR (FMA) DAN PUPUK KANDANG TERHADAP INFEKSI AKAR dan SERAPAN P PADA TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt.) - Mohamad Sony Hardi (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2020)
This study aims to determine the role of FMA and manure and their interactions with root infections and P uptake in sweet corn (Zea mays saccharata Sturt.). The study was conducted in July - September 2018 using experimental methods in the field. The experimental design used in this study was two ways completely randomized (RAL) consisting of the first factor: M0 (without mycorrhizal administration), M1 (50 FMA spores / polybags), M2 (100 FMA spores / polybags), M3 (150 spores FMA / polybag) and the second factor: K0 (Without Manure), K1 (Manure 10 tons Ha-1), K2 (Manure 15 tons Ha-1), K3 (Manure 20 tons Ha-1). Experimental data were analyzed using variance (ANOVA) at 5% significance level. The results showed that the interaction of FMA and manure affected the increase in P uptake of corn plants and P available soil. The highest P uptake of plants was obtained at the FMA 150 spore treatment and the administration of a manure dose of 15 tons Ha-1, while the highest available P soil was obtained at the FMA 150 spore treatment and the administration of a 20 ton Ha-1 manure dose. The application of FMA can increase the percentage of root infections. The highest percentage of root infection was obtained in the treatment of 150 spore FMA doses and 20 tons Ha-1manure.